Nodal marginal zone lymphoma arising in the submental region: A case report and review of literature. Issue 3 (May 2022) - Ochiai, Shunsuke; Yoshida, Shunichi; Karube, Takeshi; Sakaguchi, Tatsuya; Asano, Takahiro; Yajima, Shosuke; Muraoka, Wataru; Araki, Daisuke; Yamada, Manabu; Suga, Kenichiro; Nakagawa, Taneaki; Asoda, Seiji
Abstract: Nodal marginal zone lymphoma (NMZL) is a type of low-grade B-cell lymphoma arising in the follicular marginal zone of the lymph nodes. It is an extremely rare disease that accounts for 1.5 %–1.8 % of all malignant lymphomas. We herein report a case of nodal marginal zone lymphoma arising in the submental region. A 45-year-old woman was referred to our hospital because of swelling of the submental region. Contrast-enhanced computed tomography revealed 2 masses measuring 25 and 10 mm in diameter in the submental region, and the inside of the masses showed uniform enhancement. Magnetic resonance imaging revealed a low signal intensity on T1-weighted imaging and high signal intensity on T2-weighted images. Given these findings, the clinical diagnosis was submental tumor. We performed lymphadenectomy under general anesthesia. The histopathological diagnosis was NMZL. Subsequently, the patient was referred to the Department of Hematology, and a general examination was performed. There were no B symptoms, such as a fever or weight loss, and no lesions were found at other sites. The patient was ultimately diagnosed with Stage IA disease by Ann Arbor staging. At present, 26 months have passed, and the postoperative course has been uneventful.